2020
DOI: 10.1016/j.mehy.2020.109783
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine as an aerosol might markedly reduce and even prevent severe clinical symptoms after SARS-CoV-2 infection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 29 publications
1
36
0
7
Order By: Relevance
“…While there is no commercially available aerosolized formulation of HCQ, a recent empirical study of inhaled HCQ aerosols at 4 mg per day over one week found it was well tolerated without significant adverse events (14). This further supports the rationale of applying inhalable liposomal HCQ with direct lung targeting in COVID-19 infection/disease prevention and treatment.…”
Section: Discussionmentioning
confidence: 64%
“…While there is no commercially available aerosolized formulation of HCQ, a recent empirical study of inhaled HCQ aerosols at 4 mg per day over one week found it was well tolerated without significant adverse events (14). This further supports the rationale of applying inhalable liposomal HCQ with direct lung targeting in COVID-19 infection/disease prevention and treatment.…”
Section: Discussionmentioning
confidence: 64%
“…There are several common adverse effects associated with this medication including diarrhea, vomiting, and peripheral neuropathy 91 . Fenoterol has already been recommended to reduce severe pulmonary symptoms of COVID-19 patients 92 . Doxi uridine has been suggested as a possible SARS-CoV-2 inhibitor based on similarities with active antivirals already tested by arti cial intelligence 93 .…”
Section: Resultsmentioning
confidence: 99%
“…A small nonrandom clinical trial in France showed that HCQ combined with azithromycin has a significant therapeutic effect (Gautret et al, 2020), and it has been reported that CQ can effectively inhibit the deterioration of new coronary pneumonia, improve lung imaging performance, promote viral reversion and shorten the time of disease onset (Gao et al, 2020). It has been hypothesized that HCQ aerosols can be inhaled early in infection, allowing for the sufficient therapeutic effects on alveolar epithelial cells while avoiding the adverse effects of large oral doses (Klimke et al, 2020). However, it has also been reported that the combination of HCQ and azithromycin in 11 patients with severe 2019-nCoV infection has not achieved a positive clinical effect (Molina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%